2019
DOI: 10.1186/s13104-019-4258-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-care practices regarding diabetes among diabetic patients in West Ethiopia

Abstract: Objective To assess the self-care practices and associated factors among diabetic patients in West Ethiopia. Results A total of 252 study participants were included in the study, of this 54.8% were male. Of the participants more than half 150 (59.5%) had poor glycemic control and 153 (60.7%) of the participants had good self-care. Majority of the study participants 209 (82.9%) had adequate foot care and more than half 175 (69.4%) and 160 (63.5%) had adequate dietary pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
68
7
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 25 publications
(29 reference statements)
22
68
7
2
Order By: Relevance
“…A total of nineteen studies yielding a total study population of 6595 was eligible and included for both qualitative and quantitative analyses. Amhara, Oromia, and Hareri regions contributed 26.3%(24-28), 21% (6,11,29,30), and 157% (2,7,31) to the total of included studies, respectively. Three regions:…”
Section: Characteristics Of Included Primary Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of nineteen studies yielding a total study population of 6595 was eligible and included for both qualitative and quantitative analyses. Amhara, Oromia, and Hareri regions contributed 26.3%(24-28), 21% (6,11,29,30), and 157% (2,7,31) to the total of included studies, respectively. Three regions:…”
Section: Characteristics Of Included Primary Studiesmentioning
confidence: 99%
“…The effect of social support on diabetic self-care practice has been explored among six studies (7,8,11,25,29,36). Of these, five of the studies revealed that good social support promotes self-care practice.…”
Section: Determinants Of Diabetics' Self-care Practicementioning
confidence: 99%
See 3 more Smart Citations